Availability and Profit Analysis of 3-out-of-4 Repairable System with Preventive Maintenance - Yusuf, Ibrahim (International Journal of Applied Mathematical Research, 2012)
Studies on two unit repairable standby system dealing with availability and profit analysis involving preventive maintenance are numerous. However little attention is paid on the study of evaluation of reliability characteristics such as availability, busy period and profit function of multi component system such as 3-out-of-4 system involving four types of failures . In this paper, we studied the availability and profit analysis of a repairable redundant 3-out-of-4 system with preventive maintenance involving four types of failures and  develop explicit expressions for steady-state availability and profit function for the system using Chapman-Kolmogorov equations. Some particular cases have also been obtained analytically and graphically to see the impact of preventive maintenance on some system measures of effectiveness .Certain important result have been evaluated as special cases. Results have shown that system with preventive maintenance is better in terms of system effectiveness than system without preventive maintenance.